PERBAIKAN DEFORMASI PLAT BAJA PADA KONSTRUKSI BLOCK SS1A KAPAL CEPAT RUDAL 60M AKIBAT PROSES ASSEMBLY - Utomo, Budi (Civil Infrastructure Engineering and Architectural Design, 2019)
Construction plate that has undergone various treatments will definitely deform. Deformation can be interpreted as a change in shape that occurs because of several factors, starting from load pressure, withdrawal, lifting, and welding. In ship building is a welding work that causes the most deformation due to the influence of large heat so that the plate expands and curves quickly. If the deformation is not handled, it will change the shape of the dimensions of the ship and also affect the process of joining erection. To overcome the problem of deformation, the Fairing is done, namely the heating process and cooling the plate in extreme. The fairing process is a method that is carried out to improve the tenacity and toughness of a plate after being coldly bent. Heat treatment is needed to help restore the plate to the specified shape. So that it can minimize the occurrence of dimensional changes and prevent repair when joining erections.